Management and outcome of unknown patients with head injury in tertiary health-care center - Nikhil Khantal; Vivek Kumar Kankane; Avinash Sharma (Asian Journal of Medical Sciences, 2023)
Background: Patients who are admitted to government hospitals without any personal, family, or identification details are categorized as unknown patients or unidentified patients or destitute patients. Managing unknown patients pose unique challenges in developing countries, particularly in India, where there are significant medicolegal issues, humanitarian concerns, and treatment and rehabilitation challenges. Aims and Objectives: Our study aims to investigate the demographic characteristics and outcomes of unidentified patients in our health-care facility and to evaluate the quality of care provided to them with the intention of enhancing it. Materials and Methods: It is a prospective study conducted in the Department of Neurosurgery, Jayarogya Hospital, Gajra Raja Medical College, Gwalior, India, which is a tertiary care center. The study was conducted for a duration of 2 years between April 2021 and March 2023 in which 50 patients of traumatic brain injury (TBI) whose identity was unknown at the time of admission were analyzed. Results: Out of the 50 TBI patients with unknown identities, 21 patients survived while 29 patients died as a result of their injuries. Among the 38 patients who were managed conservatively, 17 patients survived while 21 patients died. Of the 12 patients who underwent surgery, 4 survived while 8 patients died. The stable patients who were transferred to other departments were discharged to their homes. Conclusion: Our study highlights the high mortality risk associated with unknown TBI patients. Due to the lack of crucial details about the traumatic event and the absence of a family support system, managing these patients are more challenging, and relevant health information is often unavailable. Improvements in identifying unknown victims are necessary, and resources must be allocated to address this challenging situation properly.